Correction: Synthesis of chitosan–gelatin molecularly imprinted membranes for extraction of l-tyrosine. Issue 3 (4th December 2014) - Zheng, Xue-Fang; Lian, Qi; Yang, Hua
Abstract : Correction for 'Synthesis of chitosan–gelatin molecularly imprinted membranes for extraction ofl -tyrosine' by Xue-Fang Zheng et al., RSC Adv., 2014, 4, 42478–42485.